A Database of Lapidary Artifacts in the Caribbean for the Ceramic Age. (8th June 2021) - Queffelec, Alain; Fouéré, Pierrick; Caverne, Jean-Baptiste
Lapidary artifacts show an impressive abundance and diversity during the Ceramic period in the Caribbean islands, especially at the beginning of this period. Most of the raw materials used in this production do not exist naturally on the islands of the Lesser Antilles, nevertheless, many archaeological sites have yielded such artifacts on these islands. In the framework of a four-years-long project, we created a database by combining first hand observations and analysis, as well as a thorough literature survey. The result is a database including more than 100 sites and almost 5000 beads, pendants, blanks and raw material fragments.